Elizabeth Robins : staging a life, 1862-1952 - John, Angela V. (Routledge, 1995)
A woman of extraordinary energy, talent and versatility. Elizabeth Robins was an actress who popularised Ibsen on the British stage, a prolific and popular writer of novels and non-fiction, and an Edwardian suffragette. Her extensive circle of friends included Florence Bell, Henry James, John Masefield and William Archer. She worked with the Pankhursts and knew the Woolfs. Through examining the life and work of this vivid and transatlantic figure born during the American Civil War yet surviving into the England of the 1950s, Angela John raises questions about the shaping of historical identiti.